2009
DOI: 10.1094/cchem-86-2-0225
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Physical, and Chemical Properties of Grain and Flour from Chalky Rice Mutants

Abstract: Morphological, physical, and chemical properties of grain and flour of 20 chalky rice mutants were compared with those of a translucent parental cultivar, Koshihikari. Compound starch granules were loosely packed and single starch granules were observed in chalky parts of mutant endosperm. Chalky mutant lines were classified into milky‐white and white‐core lines based on the degree of endosperm chalkiness. Physical and chemical characteristics also suggest a division of chalky mutant lines into two groups, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 14 publications
(39 reference statements)
3
82
0
1
Order By: Relevance
“…Chalkiness is linked to the process of starch accumulation in the rice endosperm (Kim et al 2000;Lisle et al 2000;Patindol and Wang 2003;Ashida et al 2009;Patindol et al 2014). In addition to the previously mentioned marketing issues, chalkiness leads to increased breakage during milling, thus reducing HRY (Counce et al 2005;Lanning et al 2011).…”
mentioning
confidence: 99%
“…Chalkiness is linked to the process of starch accumulation in the rice endosperm (Kim et al 2000;Lisle et al 2000;Patindol and Wang 2003;Ashida et al 2009;Patindol et al 2014). In addition to the previously mentioned marketing issues, chalkiness leads to increased breakage during milling, thus reducing HRY (Counce et al 2005;Lanning et al 2011).…”
mentioning
confidence: 99%
“…However, the colorimetric analysis of head rice measured with and without chalky kernels revealed that L* values did not change significantly with the exclusion of chalky kernels. Rather, the authors hypothesize that the effect of NTAT on kernel formation, that is, loose packing of starch granules (Ashida et al 2009), may be manifested not only in the obvious visibly chalky portions of kernels but also in the remaining nonchalky portions of kernels, thus influencing the translucency and whiteness of the kernels. Whiteness values trended slightly lower with the exclusion of chalky kernels, but the differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…The operator pours the kernels manually into the instrument and there are a range of discs with different cavity sizes for different sorts of rice. The quality parameter chalkiness, which is also called white belly, is a measurement of the opacity of the endosperm, which can reduce the hardness of the kernels [15,16]. Chalkiness can occupy >50% of the kernel area and can be caused by both varietal and environmental factors, such as the packing degree and morphology of the starch granules, high temperature, insufficient nutrition supply and the durability of the ripening [17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%